Analysis of Teacher Discipline Behavior in the Learning Process through Field Observations - Shalma Wafiq Azizah (Mauve Journal De Leardu, 2026)
The paper will also examine the multidimensional aspect of teacher disciplinary behavior in the learning process through a direct observation in the classroom, and how it relates to the effectiveness of the learning process. The quantitative descriptive design was used, which included six teachers observed in twelve classroom sessions using a structured observation tool which comprised of ten discipline indicators. Analytics of the data were performed with the help of the descriptive and inferential statistical methods. The results show that the general level of teacher discipline is moderate in development with better performance in administrative and structural factors like delivery of materials and adherence to rules. Conversely, interaction and compliance with teaching schedules are rather low. The correlation analysis demonstrates that discipline dimensions are related to each other, in particular, between punctuality and classroom management, or professional commitment and interaction. The novelty of the proposed study is that it utilizes observational data to investigate the concept of teacher discipline as a multidimensional construct, which offers a more objective viewpoint in comparison to self-report based approaches. The research points out the value of enhancing interactive and time-management skills in order to facilitate successful teaching and curriculum execution. These results present a theoretical contribution and practical implications on how to enhance teacher professionalism and educational quality.